DESKRIPSI PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI TINGKAT KECERDASAN LOGIS MATEMATIS - Muhammad Yali; Muhammad Ali; Evi Novianty (STKIP Paris Barantai, 2023)
The study alms to find out Mathematical Problem Solving in terms of the level of Mathematical Logical Intelligence of class VIII C students of SMP Negeri 1 Kotabaru. The type of research used was descriptive qualitative research. The subjects of the research were 2 students with a high level of logical-mathematical intelligence, 2 students in the medium category, and 2 students in the low category in class VIII C SMP Negeri 1 Kotabaru. Data collection techniques in this study were written tests and interviews. Data analysis was carried out starting from triangulation data, data reduction, presentation and then drawing conclusions. The results showed that for solving mathematical problems students with a high level of Mathematical Logical Intelligence were able to solve problems from each step of solving Polya correctly. Students in the moderate category are able to fulfill the three indicators of problem solving based on Polya's steps, even though they are not optimal. Students in the low category only fulfill two problem solving indicators based on Polya's steps. Keywords: Problem Solving, Mathematical Problems, Mathematical Problem Solving, Mathematical Logical Intelligence.